Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given the following two series:

$$1^3 + 2^3 + ... + n^3$$ $$0^3 + 1^3 + .... + (n-1)^3$$

I take the difference vertically of the two:

$$\left(1^3-0^3\right) + \left(2^3-1^3\right) + .... + \left(n^3-(n-1)^3\right)$$

This equals to $n^3$

If I now express this in sum notation:

$$\sum_{i=1}^n\left(i^3-(i-1)^3\right) = n^3$$

If I expand: $(i-1)^3 = i^3 - 3i^2 + 3i - 1$


$$\left(i^3 - (i-1)^3\right) = 3i^2 - 3i +1$$

My sum is now:

$$3\sum_{i=1}^n i^2 -3 \sum_{i=1}^n i + n = n^3$$ $$\sum_{i=1}^n i^2 = \frac{1}{3} \left(n^3 + 3 \frac{n(n-1)}{2} -n\right)$$

And the expression on the RHS above is not $\frac{1}{6} n (n+1) (2n+1)$

I don't want to solve the above using forward difference, I want to keep it backward.

share|cite|improve this question
$\sum_{i=1}^ni=\frac{n(n\color{red}{+}1)}2$. – Brian M. Scott Mar 19 at 22:32
I came here expecting "[s]eries of squares". – imallett Mar 20 at 4:49
up vote 10 down vote accepted

$$\sum_{i=1}^n i={n(n+1)\over2}\quad\text{ not }\quad {n(n-1)\over2}$$

share|cite|improve this answer
Oh God... why was I thinking about maximum number of unique pairs... – i squared - Keep it Real Mar 19 at 22:43
@isquared-KeepitReal, it's an easy mistake to make. You gave a very clear presentation of your approach, which made it easy for fresh eyes to spot the error. – Barry Cipra Mar 19 at 23:49
Thank you very much for spotting it. – i squared - Keep it Real Mar 19 at 23:55

Your error is when you evaluate $$\sum_{i=1}^n i = \frac{n(n-1)}{2}$$ The correct formula is $$\sum_{i=1}^n i = \frac{n(n+1)}{2}$$ plugging this, everything works.

share|cite|improve this answer

Note that $\sum_{i=1}^n i = \frac 12n(n{\color{red}+}1)$, hence \begin{align*} \frac 13 \left(n^3 + 3\frac{n(n+1)}2 - n\right) &= \frac 16 n(2n^2 + 3n + 3 - 2)\\ &= \frac 16 n(2n^2 + 3n + 1)\\ &= \frac 16 n(2n+1)(n+1) \end{align*}

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.